Predicting the Quality of Couples' Relationships based on Fears of Parents of Children with Cancer: A Mediating Role of Psychological Distress - Raeisipour, Zoleikha; Shafiabadi, Abdollah; Younesi Brojeni, Jalil (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to investigate the mediating role of psychological distress in the relationship between fear and the quality of marital relationships in parents of children with cancer. Methods: The present study was descriptive-correlational and had a structural equation modeling type, and its statistical population consisted of parents of all children with cancer who visited Bandar Abbas Children's Hospital in 2019. Among whom, 200 parents were selected as the sample group using the purposive sampling method. Data collection tools included the Quality of Couple Relationship Questionnaire by Khoshkam et al. (2007), the Fear Questionnaire by Marks & Mathews (1979), and the Psychological Distress Scale by Kessler et al. (2002). Data analysis was performed using Pearson correlation coefficient, and path analysis according to AMOS. Results: The results indicated that psychological fear and anxiety had a significant negative relationship with the quality of couples' relationships. Furthermore, the correlation coefficients between the quality of couples' relationships with psychological distress (r=-0.44) and fear (r=-0.30) were significant at a level of 0.01, and the correlation coefficient between fear and psychological distress (r= 0.34) was significant at a level of 0.01. Conclusion: Accordingly, programs can be developed to reduce fear and psychological distress in designing the necessary measures to improve the quality of couple relationships in parents of children with cancer.